Peranan Restrukturisasi Utang dalam Melindungi Perseroan Terbatas dari Kepailitan Berdasarkan Undang-Undang Nomor 37 Tahun 2004 - Karyn, Khanza Octalivia; Lewiandy (AL-SULTHANIYAH, 2025)
This research analyzes a fundamental academic problem in Indonesia's bankruptcy law lies in the tension between the spirit of business rescue through Suspension of Debt Payment Obligations (PKPU) and the rigidity of the "single settlement principle" which denies debtors a second chance. This study analyzes the role of debt restructuring in safeguarding Limited Liability Companies (LLCs) from insolvency under Law No. 37 of 2004. Using a normative juridical method with a descriptive-analytical approach, this research utilizes primary data from court decisions and secondary data from legal literature. This study finds that although PKPU is designed to protect debtors, the application of the single settlement principle in the UUK-PKPU limits debtors’ ability to recover, often favoring creditors with stronger bargaining positions. This creates a legal vulnerability where good-faith debtors are immediately bankrupted upon the failure of a reconciliation plan without further legal recourse. Therefore, a renegotiation mechanism should be allowed to give debtors the opportunity to preserve their businesses.